Changes following adversities: the role of religious coping in the lives of homeless women of Vrindavan (India) - Rana, Neetu (2016)
There are 17,571 homeless women in Vrindavan, a major pilgrimage town in North India (State Government Report, 2012). The town is spread across 4.56 square kilometers and the number of homeless women is increasing continually (NCW, 2010). The living conditions are inadequate and the majority live below the poverty line (Rai, 2010). In the last two decades, various attempts have been made by the government and non government organizations to build physical amenities, but psychological well being remains ignored (Rana & Misra, 2010). In literature, these women have often been portrayed as the victims of various tragedies, presenting only the vulnerable side. The present thesis attempts to explore the thriving side of these women, along with the vulnerable one. This thesis aims to study the changes, following various adversities, which homeless women of Vrindavan have faced in their lifetime. The study takes a critical stance of the medical model of negative changes following adversities, and endorses the understanding offered by positive psychology. Within positive psychology, the present thesis rejects the use of the term ‘Posttraumatic Growth’ because of the medical and universal implications that the term “trauma” brings, ignoring the cultural differences. Therefore, ‘Changes Following Adversities’ is used as the preferred term.